Arctic conflict and co-operation. (2nd January 2023) - Medby, Ingrid A.
ABSTRACT: The Arctic region is often presented as a space either of future conﬂict or of exceptional co- operation. While Arctic experts have long argued for more nuanced understandings of the region, Russia's invasion of Ukraine in 2022 once more brought these questions to the fore. This article challenges the assumption that the Arctic is either one or the other. Instead, it highlights how a diverse Arctic region is one of equally diverse relations, peoples, places and events – and of multiple imaginaries all at once. It argues that appreciating the complexities of socio-political relations is now more important than ever – and that Arctic conﬂict or co-operation, neither or both, is not pre- determined .